An approach to innovative eSports from a business perspective - M. Ángeles López-Cabarcos; Jérôme Caby; Sergi A. Sixto Lugilde; Juan Ramón Pi\~neiro Chousa (Journal of Innovation & Knowledge (JIK), 2024)
eSports, as a competitive activity related to the video game industry has attracted significant attention in recent years. Using co-citation analysis of references and authors, bibliographic coupling of sources, and author keyword co-occurrence analysis, this paper aims to carry out a bibliometric study using information extracted from the Web of Science database between 2010 and 2022 to provide an overview of the current knowledge structure of eSports and its evolution over time from a specific perspective related to Business, Management and Economic (BM&E) issues. This analysis reveals that the current body of literature focuses primarily on key aspects, such as defining eSports, differentiating them from traditional sports, and exploring their commercial potential within the entertainment industry. This study contributes to the advancement of knowledge related to the BM&E-eSports research field by providing information on the lack of theoretical foundations, current trends, and potential future research directions. The practical implications of this study can help both researchers identify the most relevant topics and key aspects in the BM&E-eSports research field and help business managers make appropriate decisions and design effective strategies to manage eSports organizations. Overall, this research lays the foundation for future studies that aim to understand the business potential of eSports and its impact on the market and society.
Keywords: M15; O33; L83; 650; eSports; Bibliometric study; Videogaming; Management-business-economic perspective